The Effect of Company Size, Profitability, Liquidity, and Financial Leverage on Income Evaluation Action - Diamond Lianna Alifatmaya; Syaiful Syaiful (INNOVATION RESEARCH JOURNAL, 2020)
This study aims to analyze and examine the Influence of Company Size, Profitability, Liquidity, and Financial Leverage on Income Smoothing Actions. This study uses four independent variables such as Company Size, Profitability, Liquidity, and Financial Leverage and the dependent variable that is income smoothing actions. Index Excel is used to determine the income smoothing practice. Types of data are secondary data and the method of analysis used multiple linear regression. Based on the results of multiple linear regression analysis the results of the study concluded company size and profitability don't affect income smoothing. While liquidity and financial leverage affect income smoothing. For further research, it is recommended to add relevant variables in influencing income smoothing actions, consider the research period, and add to the research sample.